PERTANGGUNGJAWABAN HUKUM ANAK PELAKU TINDAK PIDANA PEMBUNUHAN YANG MENGALAMI POST TRAUMATIC SYNDROME DISORDER - Santoso, Aji Wahyu; Setyorini, Erny Herlin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Legal protection for children in conflict with the law is specifically provided by the state in the form of restorative justice through diversion. The process of resolving cases using diversion is a diversion from the judicial process to outside the judiciary. This study uses a normative method with a statutory, conceptual and case approach with decision number 9/pid.sus-anak/2020/pt dki. A 14 (fourteen) year old female teenager kills a 5 (five) year old toddler, the perpetrator who has Post traumatic syndrome disorder. Post traumatic syndrome disorder is a psychological disorder in a person after experiencing a traumatic event in his life that causes ongoing psychological stress. The judge in imposing a sentence must pay attention to the child’s needs because the Law on the Juvenile Criminal Justice System must emphasize education children and moral development. A criminal decision cannot be imposed solely on the basis of a legal basis, because the values ??of justice and truth are not sufficient to compensate for losses caused by legal actions or correctness. Elements such as social, psychological, criminological, and philosophical considerations must also be examined, apart from the reasons why the perpetrator committed the crime